Women As a Thing in Shakespearean Drama: Analytical Study - Al-Wazir, Abd Al-Rahman Badr (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The study explores how Shakespeare portrayed women as objects by using the explanations about ‘things’ from Slavoj Žižek’s feminist perspective. Through qualitative analysis and critical discourse methods, the researcher examines main female figures in Hamlet, Othello, Macbeth, A Midnight’s Summer and Antonio and Cleopatra. A major issue is that women are treated like objects and portrayed as satisfying male desires or copying how society expects them to act which helps to support patriarchal ideology. The study brings out how, according to Žižek, his idea of the ‘thing’ helps to explain the many layers of how women are portrayed. Through their exceptional talent for depicting human behaviour, Lady Macbeth, Ophelia, Gertrude, Desdemona and Emilia illustrate women’s status in a male-dominated society. These female characters, with their depth and complexity, surpass the constraints of their era, making their stories timeless. The objectification of this raises tragic results, ranging from betrayal to loss of identity. His female characters, while often shown as passive, also move against and flip typical feminine roles, exposing extra psychological difficulties for both, but especially for the women. Conclusively, the research reveals more detail about women’s roles in Shakespeare’s plays, noting they are shown as more than simple objects in the story. It actually reflects wider society’s concerns about being feminine and in charge. Positioning Shakespeare’s dramas alongside Žižek’s theory encourages new methods of exploring issues at the crossroads of gender, desire and ideology in early modern writing, as well as their continuing importance in current thought.